An introduction to political theory - Mukhopadhyay, Amal Kumar (SAGE Publications, 2019)
"A precise, analytical and critical account of the fundamentals of political theory and the major concepts used in political analysis. This book offers an introduction to major political theories for the first learners of political science at the graduate level as well as those interested in building a strong groundwork of the subject. It cites Indian and global examples and discusses real-life applications of these theories to make the theories and concepts relatable and approachable. The book offers a compact overview of the concepts of state, society, civil society, justice, law, freedom, equality and others along with critical discussions on premier political ideologies of Marxism, Liberalism, Anarchism, Fascism, Gandhism and much more. Enriched by the author's long-term experience in research and teaching on the subject, this textbook will prove to be an essential companion for students of political science, sociology and social work as well as Civil Services aspirants. Key Features: Special focus on Indian political theory and the course of its development; Encourages the readers to ponder and debate further; Presents a practical perspective, by contextualizing the theories within real-life situations. Amal Kumar Mukhopadhyay, Retired Principal and Professor of Political Science, Presidency College (now Presidency University), Kolkata"--